IEEE EDUCON 2010 Conference 2010
DOI: 10.1109/educon.2010.5492410
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint identification in LMS and its empirical analysis of engineer students' views

Abstract: This paper describes a fingerprint identification system (FIS) developed to be integrated in learning management system (LMS). Hence, a middleware is necessary to connect any LMS with our own FIS, which will provide us a scalable, robust, easy integration in any LMS. This project aims to solve the problems of identity authentication of users in remote or virtual environments whose use has spread both in distance education and traditional universities. It seeks its integration into traditional and remote enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Gil et al [9] described a fingerprint identification system (FIS) developed to be integrated in learning management system (LMS). Hence, a middleware is necessary to connect any LMS with their own FIS, which will provide them a scalable, robust, easy integration in any LMS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gil et al [9] described a fingerprint identification system (FIS) developed to be integrated in learning management system (LMS). Hence, a middleware is necessary to connect any LMS with their own FIS, which will provide them a scalable, robust, easy integration in any LMS.…”
mentioning
confidence: 99%
“…This study intends to narrow this gap. Therefore, this research is developed to eliminate the need for a middleware as found in study [9]. This is achieved by introducing a Single Sign-On approach.…”
mentioning
confidence: 99%